Strategi Indonesia Menghadapi Hambatan Non-Tarif Uni Eropa Terhadap Ekspor Crude Palm Oil (CPO) Tahun 2017-2019 - Krisna Bhaskara, I Komang Bagus; Putri, Penny Kurnia; Suwecawangsa, Adi Putra (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2020): Jurnal Hubungan Internasional 2020, 2020)
This study aims to describe Indonesia's strategy in dealing with EU non-tariff barriers to Indonesia's CPO exports using the qualitative method. The EU implemented non-tariff barriers to Indonesia's CPO imports from 2009-2017. However, Indonesia has only been aggressively responding and implementing strategies in dealing with EU obstacles since 2017. This is because there has been a direct negative impact on the Indonesian economy, including a decrease in the value of CPO exports. Therefore, the researcher uses the framework of public relations campaign and new protectionism in free trade to answer Indonesia's strategy in facing EU obstacles in 2017-2019. This study then found the answer that Indonesia's strategy was carried out through a positive campaign or white campaign to EU countries and also made a counter policy, namely protecting nickel.   Keywords: Indonesia, European Union, Campaign, New Protectionism